Antitumor effects of circ‐EPHB4 in hepatocellular carcinoma via inhibition of HIF‐1α. Issue 6 (18th February 2019) - Tan, Yuhui; Du, Biaoyan; Zhan, Yujuan; Wang, Kun; Wang, Xiaolan; Chen, Bonan; Wei, Xianli; Xiao, Jianyong
Abstract : The protein EPHB4 plays a vital role in various tumor types. However, few studies into the function of circ‐EPHB4 (hsa_circ_0001730) in tumors have been conducted. This study aimed to investigate the functions of circ‐EPHB4 and the underlying mechanism of circ‐EPHB4 in regulating hepatocellular carcinoma (HCC). The expression of circ‐EPHB4 was found to be downregulated in HCC tumor tissues, whereas circ‐EPHB4 overexpression suppressed cell viability, induced apoptosis, and inhibited cell migration and invasion in Huh7 and HepG2 cells. circ‐EPHB4 levels were negatively correlated with tumor weight, size, and metastasis foci in nude mouse models, suggesting circ‐EPHB4 inhibits tumorigenesis, tumor development, and metastasis. In addition, HIF‐1α and PI3K–AKT pathways were markedly affected by circ‐EPHB4 overexpression. HIF‐1α could potentially be the target of circ‐EPHB4. By overexpressing both HIF‐1α and circ‐EPHB4, the antitumor effect of circ‐EPHB4 should be most probably correlated with HIF‐1α. In conclusion, circ‐EPHB4 is a tumor inhibitor in HCC and functions by inhibiting HIF‐1α expression.